2013
DOI: 10.7763/ijbbb.2013.v3.178
|View full text |Cite
|
Sign up to set email alerts
|

The Comparison of Plant Regeneration between Jerusalem Artichoke and Purple Potato Cultured on MS Media with Different Concentrations and Combinations of Plant Growth Regulators

Abstract: Abstract-A deeper understanding of the influence of culture media and different germplasm is crucial to propagate the plants in vitro conditions. To focus this, two tuberous plant species; Jerusalem artichoke (Helianthus tuberosus) and Purple potato (Solanum tuberosum) were selected. In the present study, stem segments from two species selected as explant source were cultured on Murashige and Skoog's media containing various concentrations (0.2 and 0.5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…It is concluded that R 4 achieved the highest values for rooting percentage, roots length and roots number, respectively for all cultivars and the Alba was the best. Contrary, Karadag et al (2013) noticed that root formation of tuberous plants was enhanced using gibberellic acid. Where, the regenerated plantlets of J. artichoke were rooted efficiently on MS medium containing 1.0mg L -1 gibberellic acid.…”
Section: In Vitro Rootingmentioning
confidence: 94%
See 1 more Smart Citation
“…It is concluded that R 4 achieved the highest values for rooting percentage, roots length and roots number, respectively for all cultivars and the Alba was the best. Contrary, Karadag et al (2013) noticed that root formation of tuberous plants was enhanced using gibberellic acid. Where, the regenerated plantlets of J. artichoke were rooted efficiently on MS medium containing 1.0mg L -1 gibberellic acid.…”
Section: In Vitro Rootingmentioning
confidence: 94%
“…literatures on in vitro propagation of J. artichoke due to one or more greatest challenges (in vitro hyper-hydricity; Abdalla et al, 2014), the long period of dormancy (about 4-6 months; Kays & Nottingham, 2008) and high contamination rate (Abdalla et al, 2014). The previous few studies have reported that the in vitro propagated J. artichoke could be achieved on a simple nutrient medium by repeated subcultures from axillary meristems of in vivo growing plants (Gamburg et al, 1999); somatic embryogenesis (El Mostafa et al, 2008); in vitro regeneration (Karadag et al, 2013). The in vitro plantlets provided stem node segments for micro-tubers formation (Gamburg et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, V. turcica was grown from unfertilized ovary explants, which were taken from Nezahat Gökyiğit Botanical Garden (NGBG) of Istanbul in Turkey. It is known from previous studies that micropropagation of V. turcica using its diploid explants such as rhizome, leaf, and epicotyl has already been conducted (Cenkci et al 2009;Karadag et al 2013). However, plant propagation using unfertilized ovary explants of V. turcica is the first attempt in this study.…”
Section: Introductionmentioning
confidence: 90%